2016
DOI: 10.3390/jfb7040034
|View full text |Cite
|
Sign up to set email alerts
|

Use of Micropatterned Thin Film Nitinol in Carotid Stents to Augment Embolic Protection

Abstract: Stenting is an alternative to endarterectomy for the treatment of carotid artery stenosis. However, stenting is associated with a higher risk of procedural stroke secondary to distal thromboembolism. Hybrid stents with a micromesh layer have been proposed to address this complication. We developed a micropatterned thin film nitinol (M-TFN) covered stent designed to prevent thromboembolism during carotid intervention. This innovation may obviate the need or work synergistically with embolic protection devices. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, the further growth of cell populations proceeds better on smoother surfaces (of the LP series). This can be explained by easier cell motion over short distances on a smoother surface in The obtained results are in good agreement with study [52], where the dynamics of the interaction of cell populations with the surface of an alloy based on TiNi was considered. This study showed that implantable devices with a microroughness of 20-145 µm could successfully resist embolism.…”
Section: Cell Growth Experimentssupporting
confidence: 87%
“…However, the further growth of cell populations proceeds better on smoother surfaces (of the LP series). This can be explained by easier cell motion over short distances on a smoother surface in The obtained results are in good agreement with study [52], where the dynamics of the interaction of cell populations with the surface of an alloy based on TiNi was considered. This study showed that implantable devices with a microroughness of 20-145 µm could successfully resist embolism.…”
Section: Cell Growth Experimentssupporting
confidence: 87%
“…Stents are metallic tubular scaffolds or meshes that restore blood flow to the surrounding tissues by unblocking diverse blood vessels such as coronary, iliac, carotid, aorta, and femoral arteries. [48][49][50][51][52][53][54][55][56][57][58] Self-expanding NiTi and stainless-steel stents are frequently used to treat atherosclerotic vessels. NiTi stents' advantage over stainless steel ones is that they do not require balloon dilation, which risks more damage to the vascular tissue due to elastic recoil and dissection (Figure 2B-i).…”
Section: Medical Applications Of Smps and Smasmentioning
confidence: 99%
“…Subsequently, the sacrificial material and etchants/solvent 16 , are chosen such that the sacrificial material can be selectively etched/dissolved without damaging the main structure. Copper (Cu) as a sacrificial material, in the lift-off process, has been used for fabrication of nitinol microelectromechanical systems (MEMS) 17 , and micropatterned thin films 18 , 19 . The latter two reports 18 , 19 investigated the use of Cu as a sacrificial layer for fabrication of thin and thick film patterned NiTi.…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu) as a sacrificial material, in the lift-off process, has been used for fabrication of nitinol microelectromechanical systems (MEMS) 17 , and micropatterned thin films 18 , 19 . The latter two reports 18 , 19 investigated the use of Cu as a sacrificial layer for fabrication of thin and thick film patterned NiTi. Such patterned NiTi films were also suggested 19 to be used as an additional layer in covering stents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation